2006
DOI: 10.1590/s1519-566x2006000300002
|View full text |Cite
|
Sign up to set email alerts
|

Uncapping activity of Apis mellifera L. (Hymenoptera: Apidae) towards worker brood cells infested with the mite Varroa destructor Anderson & Treuman (Mesostigmata: Varroidae)

Abstract: PALAVRAS-CHAVE: Comportamento higiênico, varroosis, infestação natural, abelha africanizadaABSTRACT -Varroosis, a disease caused by the mite Varroa destructor Anderson and Treuman has killed hundreds of thousands of Apis mellifera L. colonies in various parts of the world. Nevertheless, the damage caused by this mite varies with the type of bee and climate conditions. Varroa causes little damage to Africanized bee colonies in Brazil, as the infestation rates are relatively stable and low. We evaluated the hygi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Moretto et al (1993) showed that Africanized bees show 38% cleaning capacity, while Italian bees only 5%. Moretto et al (2006) found that the daily rate of cells without operculum was 3.5 times greater in beehives infested with Varroa compared with non-infested beehives. This shows that Africanized bees have the ability to recognize and remove offspring naturally parasitized with the mite.…”
Section: Discussionmentioning
confidence: 90%
“…Moretto et al (1993) showed that Africanized bees show 38% cleaning capacity, while Italian bees only 5%. Moretto et al (2006) found that the daily rate of cells without operculum was 3.5 times greater in beehives infested with Varroa compared with non-infested beehives. This shows that Africanized bees have the ability to recognize and remove offspring naturally parasitized with the mite.…”
Section: Discussionmentioning
confidence: 90%
“…Despite decades of research on the hygienic behaviour towards mite-infested brood (Boecking and Drescher, 1991;Moretto et al, 2006;Peng et al, 1987;Spivak, 1996), the situation has been and still is much more difficult with V. destructor because here two possible triggers are present in each infested brood cell: the ectoparasitic mite and the affected brood. It was suggested that reproduction of the parasitising mother mite in the capped cell influences the probability of detection and subsequent removal of infested brood (Harbo and Harris, 2005) but results of more recent studies do not support this notion Ibrahim et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This was more frequently the case in the presence of adult A. cerana workers than in their absence, excluding an artifact of experimental infestation. This phenomenon could be due to a social immunity mechanism consisting in adult workers uncapping infested cells to remove V. destructor foundress mites and subsequently recapping these cells (Corrêa-Marques & De Jong, 1998;Moretto, Guerra, & Bittencourt, 2006;Oddie, Dahle, & Neumann, 2017;Rath & Drescher, 1990). As a result of parasite departure or removal from its reproduction site, remaining brood developed normally and was not removed by adult workers.…”
Section: Abnormal Development Of Infested Worker Brood Could Triggementioning
confidence: 99%